Synthesis and Characterization of Sucrose-Modified CaO Catalyst Derived from Dolomite for Transesterification of Reutealis trisperma Oil - Nuni Widiarti; Belia Anggi Sri Julianti; Mohammad Alauhdin; Yuan Maylia Rosanti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
This study presents a novel method for synthesizing solid base catalysts by modifying calcium oxide (CaO) from dolomite via a sucrose-mediated hydrothermal process. In this approach, sucrose acts as a complexing agent to remove magnesium ions (Mg²⁺), a structure-directing agent, and a carbon-based template. After Mg²⁺ removal, calcium species were recovered through coprecipitation using sodium carbonate. The synthesized catalysts were characterized to evaluate their structure using X-ray diffraction (XRD), identify functional groups via Fourier-transform infrared spectroscopy (FTIR), observe morphology and elemental composition through scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), measure particle size distribution by particle size analysis (PSA), and determine surface area through Brunauer-Emmett-Teller (BET) analysis. The catalysts exhibited a surface area of 27.411 m²/g and reduced crystallite size, both contributing to enhanced catalytic activity. In the transesterification of Reutealis trisperma oil under optimal conditions (65 °C, 3 hours, methanol-to-oil ratio 9:1), the catalyst achieved 99.40% oil conversion and 88.82% biodiesel yield. A catalyst dosage of 7.5 wt% was optimal, while higher amounts caused emulsion and soap formation due to viscosity-related mass transfer limitations. This environmentally friendly synthesis route offers a reusable catalyst system for sustainable biodiesel production from non-edible feedstocks.